ELIZABETH ISLAND: TRAVELERS, ARCHAEOLOGICAL RECORDS AND CULTURAL GEOGRAPHY - Borrero, Luis A.; Morello Repetto, Flavia; San Roman Bontes, Manuel Julio; Mcewan, Colin; Martin, Fabiana Maria (My University, 2019)
The historic, ethnographic and archaeological information on the Elizabeth Island, Strait of Magellan, Chile is presented, with an emphasis on the location of the island on the eastern limit of the distribution of patagonian and fuegian maritime hunter-gatherers. Taphonomic and formational observations were also made. The diversity of archaeological materials recorded on the island is highlighted, including elements attributable to both maritime and terrestrial hunter-gatherers. Finally, the place of the island within the cultural geography of the region is considered, discussing its relationships with other islands of the Magellan Strait and the continent.
Keywords: patagonia; tierra del fuego; strait of magellan; archaeology; hunter-gatherers; taphonomy